Population‐based screening for Lynch syndrome in Western Australia. Issue 5 (24th February 2014) - Schofield, Lyn; Grieu, Fabienne; Amanuel, Benhur; Carrello, Amerigo; Spagnolo, Dominic; Kiraly, Cathy; Pachter, Nicholas; Goldblatt, Jack; Platell, Cameron; Levitt, Michael; Stewart, Colin; Salama, Paul; et al.
<x xml:space="preserve">Abstract</x> We showed earlier that routine screening for microsatellite instability (MSI) and loss of mismatch repair (MMR) protein expression in colorectal cancer (CRC) led to the identification of previously unrecognized cases of Lynch syndrome (LS). We report here the results of screening for LS in Western Australia (WA) during 1994–2012. Immunohistochemistry (IHC) for loss of MMR protein expression was performed in routine pathology laboratories, while MSI was detected in a reference molecular pathology laboratory. Information on germline mutations in MMR genes was obtained from the state's single familial cancer registry. Prior to the introduction of routine laboratory‐based screening, an average of 2–3 cases of LS were diagnosed each year amongst WA CRC patients. Following the implementation of IHC and/or MSI screening for all younger (<60 years) CRC patients, this has increased to an average of 8 LS cases diagnosed annually. Based on our experience in WA, we propose three key elements for successful population‐based screening of LS. First, for all younger CRC patients, reflex IHC testing should be carried out in accredited pathology services with ongoing quality control. Second, a state‐ or region‐wide reference laboratory for MSI testing should be established to confirm abnormal or suspicious IHC test results and to exclude sporadic cases by carrying out BRAF mutation or MLH1 methylation testing. Finally, a state or regional LS coordinator is essential to ensure that all appropriate cases identified by laboratory testing are referred to and attend a Familial Cancer Clinic for follow‐up and germline testing.